Money Politics Crimes in Elections from the Perspective of Dignified Justice - Wartoyo, Fransiskus Xaverius; Ginting, Yuni Priskila (SASI, 2023)
Introduction: The practice of monetary politics in all political events makes it impossible to distinguish the implementation of the mechanism of legal politics from monetary politics.Purposes of the Research:  In summary, there is a general assumption that money politics in any political competition is natural, even unavoidable. The detention of monetarism can be done through crime prevention theory from the point of view of proper justice theory. Methods of the Research: The type of research used is legal research. The phenomenological method is a study that aims to determine the nature of a phenomenon experienced by several individuals.Results of the Research: Bawaslu's efforts against money politics in holding legislative elections take two forms, namely prevention efforts and law enforcement efforts as a form of monitoring parliamentary elections.